CONVERGENCE AND HYBRIDIZATION OF PROJECT MANAGEMENT METHODOLOGIES - S. Bushuyev (Astana IT University, 2020)
The subject of this article is the development of hybrid methodologies for managing projects, programs and project portfolios. Significant reductions in the life cycles of infrastructure programs, which contain projects of various lines of activity and various management methodologies, for example, waterfalls with a rigid life cycle and Agile with a flexible methodology life cycle, require the use of convergence tools to form “hybrid” methodologies. The goal is to develop a convergent approach to building hybrid project management methodologies in terms of decision-making processes in project management based on various platforms. The results of the study were obtained based on of using a convergent approach to build a methodology for managing infrastructure projects and programs. A substantial model of the obtained hybrid methodology for project and program management is presented. Conclusions: Hybrid methodologies for project and program management are becoming more popular in this category of programs. The main reason is the presence in the program of components with different life cycles, and, consequently, methodologies that require integration and harmonization. The methodology is tested by the practice of using the mechanisms of hybrid multi-level systems for managing infrastructure projects and programs. A study of hybrid project and program management methodologies defined by the practice of introducing various, in fact, program components. The use of a hybrid project management methodology allowed the authors to carry out various, in fact, projects on time with a specified budget. On the example of complex construction projects and projects for the creation of information and communication infrastructure management systems. Further areas of research are associated with a detailed study of the mechanisms of harmonization, integration, convergence and updating.